2021
DOI: 10.1038/s41598-021-95478-6
|View full text |Cite
|
Sign up to set email alerts
|

The full phase space dynamics of a magnetically levitated electromagnetic vibration harvester

Abstract: We consider the motion of an electromagnetic vibrational energy harvester (EMVEH) as function of the initial position and velocity and show that this displays a classical chaotic dynamical behavior. The EMVEH considered consists of three coaxial cylindrical permanent magnets and two coaxial coils. The polarities of the three magnets are chosen in such a way that the central magnet floats, with its lateral motion being prevented by enclosion in a hollow plastic tube. The motion of the floating magnet, caused by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…a mean absolute percentage error of 6% has been demonstrated [204]. Most current-state devices are in the centimeter range and produce a voltage in the mV-V range and power in the mW range [202], although this depends on the exact way that the device is operated as EMEH devices can have a quite complex phase space [205].…”
Section: Devicementioning
confidence: 99%
“…a mean absolute percentage error of 6% has been demonstrated [204]. Most current-state devices are in the centimeter range and produce a voltage in the mV-V range and power in the mW range [202], although this depends on the exact way that the device is operated as EMEH devices can have a quite complex phase space [205].…”
Section: Devicementioning
confidence: 99%
“…Thus, the 2D-EMVEH is like the 1D-EMVEH, a magnetic spring-like system with a damping force from the coil windings. In 1D an EMVEH harvester is governed by the following sets of equations [16]:…”
Section: Physics Of the 2d-emvehmentioning
confidence: 99%
“…The magnetic restoring force is usually modeled as the Duffing hard characteristics [20]. A study [21] demonstrated that a magnetic levitation vibrational energy harvester exhibited features that were typical of chaotic dynamic systems. However, the state was more complicated than the Duffing equation, which was previously used to describe magnetic forces.…”
Section: Introductionmentioning
confidence: 99%